Coxsackievirus B infections are common in Cystic Fibrosis and experimental evidence supports protection by vaccination - Virginia M. Stone; Renata Utorova; Marta Butrym; Amir-Babak Sioofy-Khojine; Minna M. Hankaniemi; Emma E. Ringqvist; Marfa Blanter; Anirudra Parajuli; Terezia Pincikova; Björn Fischler; Ferenc Karpati; Vesa P. Hytönen; et al. (iScience, 2022)
Summary: Viral respiratory tract infections exacerbate airway disease and facilitate life-threatening bacterial colonization in cystic fibrosis (CF). Annual influenza vaccination is recommended and vaccines against other common respiratory viruses may further reduce pulmonary morbidity risk. Enteroviruses have been found in nasopharyngeal samples from CF patients experiencing pulmonary exacerbations. Using serology tests, we found that infections by a group of enteroviruses, Coxsackievirus Bs (CVBs), are prevalent in CF. We next showed that a CVB vaccine, currently undergoing clinical development, prevents infection and CVB-instigated lung damage in a murine model of CF. Finally, we demonstrate that individuals with CF have normal vaccine responses to a similar, commonly used enterovirus vaccine (inactivated poliovirus vaccine). Our study demonstrates that CVB infections are common in CF and provides experimental evidence indicating that CVB vaccines could be efficacious in the CF population. The role of CVB infections in contributing to pulmonary exacerbations in CF should be further studied.